Structural Analysis of Import Oil and Gas in Indonesia - Naidhisyia Azzahra; Mahrus Lutfi Adi Kurniawan (Pusat Pengkajian Ekonomi dan Kebijakan Publik, 2023)
As a world crude oil exporter, Indonesia can only meet domestic oil needs of 40% and 60% through imports. The level of imports in the oil and gas sector, which is higher than exports, impacts the trade balance, which can threaten the stability of the domestic economy. This study analyzes oil and gas import policies using time-series data from 2005Q1-2021Q4 using the VECM approach. The study results show that GDP, inflation, world oil prices, and interest rates affect oil and gas imports. Structural analysis shows that inflation and world oil prices are essential in oil and gas import policies. The implications of the research show that apart from political policies, decisions on oil and gas imports must also pay attention to conditions of domestic inflation and international oil prices to stabilize domestic economic conditions.